INQUIRY TRAINING BASED E-MODULE DEVELOPMENT IN SCIENCE SUBJECTS TO IMPROVE HOTS LITERACY ABILITY OF CLASS IV SCHOOL STUDENTS BASE - John Simon Sinulingga; Retno Dwi Suyanti; Sriadhi Sriadhi (Sensei International Journal of Education and Linguistic, 2023)
The purpose of this study was to determine the feasibility and effectiveness of Inquiry Training-based E-Modules in science subjects to improve HOTS literacy skills for Class IV Elementary School students. This research is a type of research and development (Reasearch and Development) using the ADDIE model ( Analysis, Design, Development, Implementation, Evaluation ). The results showed that the E-Module based on Inquiry Training in science subjects to improve HOTS literacy skills was "Very Eligible" with details of the average score given by design experts 4, 4 in the "Very Good" category with a feasibility presentation of 88 % with “Very Eligible” category. The material expert validation results were 4.56 in the "Very Good" category and the feasibility presentation rate was 91% in the "Very Eligible" category. And based on the results of the pre-test and post-test there was an increase in presentation of 29.3 %. Initial pre-test results were 5 4.5 % and post-test results were 8 4 %. Therefore it can be concluded that Inquiry Training-based E-Modules in science subjects to improve HOTS literacy skills are appropriate and effective for use in the learning process